Association between workplace violence from patients and the mental health status of healthcare workers in Zhuhai China: a cross-sectional study - Ying Zheng; Xuping Li; Yajun Sun; Yajun Sun; Chun Mao; Chun Mao; Jiaju Huang; Jiaju Huang; Jingya Li; Guangchuan Zhang; Guangchuan Zhang; Ning Wei; et al. (Frontiers in Public Health)
ObjectiveWorkplace violence (WPV) poses a serious occupational risk. This study aims to explore the association between WPV from patients and the occurrence of insomnia, depression, and anxiety among healthcare workers.MethodsInformation about the WPV from patients was collected by a self-designed questionnaire. Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and Insomnia Severity Index (ISI) were used for the assessment of mental health. Logistic regression was used to explore the association between WPV from patients and insomnia, depression, and anxiety. Mediation analysis was used to evaluate the mediation effect of depression and anxiety on the relationships between WPV from patients and insomnia.ResultsOf 10,413 included healthcare workers, 40.05% experienced verbal violence, 6.44% experienced physical violence from patients in the past year. There is a significant association between verbal violence and insomnia (OR = 1.780, 95% CI: 1.591–1.990), depression (OR = 1.823, 95% CI: 1.640–2.026), and anxiety (OR = 1.831, 95% CI: 1.606–2.087), as well as physical violence (insomnia: OR = 1.220, 95% CI: 1.002–1.481; depression: OR = 1.274, 95% CI: 1.052–1.540; anxiety: OR = 1.316, 95% CI: 1.058–1.630). Moreover, depression and anxiety mediated the relationship between WPV and insomnia, the mediated proportion was 62.21% in the association between verbal violence and insomnia, and 60.22% in the association between physical violence and insomnia.ConclusionsThe association between WPV from patients and heightened risks of mental health issues emphasizes the necessity of supportive work environments. Recognizing the mediating role of depression and anxiety stresses the significance of tailored mental health training for healthcare staff.